Does Delayed Retirement Affect Youth Employment? Evidence from Italian Local Labour Markets - Marco Bertoni; Giorgio Brunello (Institute of Labor Economics (IZA), 2017)
Pension reforms that raise minimum retirement age increase the pool of senior individuals aged 50+ who are not eligible to retire from the labour market. Using data from Italian provinces and regions and an instrumental variable strategy, we estimate the effects of local changes in the supply of workers aged between 50 and minimum retirement age on youth, prime age and senior employment. Results based on provincial data from 2004 to 2015, a period characterized by declining real GDP, indicate that adding one thousand additional senior individuals to the local labour supply reduces employment in the age group 16-34 by 189 units. Estimates based on longer regional data covering the period 1996 to 2015, that includes also a period of growing real GDP, show smaller negative effects for young workers, suggesting that the employment costs of pension reforms may be lower when the economy is growing.
Keywords: J26; H55; J21; J14; J11; 330; pension reforms; lump of labour; youth employment; local labour markets